Narratives of Access : A Critical Exploration of How Institutional Interactions with Students Affect Regional Student Participation in Higher Education. - Ostini, Jenny; Partridge, Helen; Kelly, Kate; Owen, Sue; Jeffries, Sandra (Student Success v.11 n.2 p.60-71 https://doi.org/10.5204/ssj.v11i2.1334, 2020)
This article examines the narratives that drive university staff understanding of the concerns and experiences of regional and remote students at five universities in Australia. Interviews were conducted with thirty university staff members over a period of three months in 2018. Reflexive thematic analysis of the stories told by staff of supporting regional students found that staff used the lens of access to create meaningful stories for themselves and others in how they supported students. Access is defined as a multi-faceted term encompassing access to people, Internet, study materials and equipment and study environments. Access is facilitated by a sense of belonging or identity as a student and limited by the lack of this. Our analysis of "belongingness" draws on Bourdieu's concepts of habitas to start to unpick the interactions between higher education institutions and the student that develop student identities as scholars and centres the narrative on the student as a person, wrestling to gain many forms of access within complex social situations. [Author abstract]